Perubahan UU No.16/2019 Tentang Batasan Minimum Pernikahan - Noor Izzati Amelia; Nur Najwa; Nor Harika (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
In general, there are many marriages in Indonesia with various kinds and ages. Many underage marriages also occur in Indonesia because there are still many people who do not understand the importance of the age of adulthood to enter into marriages, causing many impacts from underage marriages. The impact is that there are many divorces, death for the mother and child due to the age for the mother who is too young and does not have the physical and mental strength so that it can interfere with the child in her womb. Marriage which takes place among minors is one of the phenomena that is very common in social life which is very widespread everywhere, both in urban and rural areas. Because some of the people who still do not understand the impact that will arise as a result of underage marriages consider underage marriages to be normal. The purpose of writing this journal is to find out the changes to Law NO.16/2019 regarding the minimum limit for marriage. The research method used is normative juridical with a statute approach. The data used is secondary data which examines library materials originating from laws and regulations, government regulations, books, journals, and mass media which are arranged into sentences and grammar that are interrelated with legal research.